Study on Mechanical Properties of Concrete-Filled Steel Tubular Members under Axial Tension - Huaguo Gao; Lingxin Zhang; Xiuchun Wang; Renjie Sun; Qingli Wang; Lu Yang (Advances in Materials Science and Engineering)
At present, the concrete-filled steel tube structure has been widely used in various practical projects. Due to the low tensile strength of the core concrete of round steel tube concrete (CFST) specimens, the axial tensile performance of CFST specimens is far from superior to its compressive performance. However, in practical projects, the concrete-filled steel tube members bearing tensile load often appear. In order to study the axial tensile properties of CFST specimens, the axial tensile tests of 5 CFST specimens and 1 pure steel tube specimen were carried out with steel tube diameter and concrete strength as variation parameters. The results show that the bearing capacity of CFST specimens is increased by 7.5%–16.3% compared with that of pure steel tube specimens with the same cross-sectional area, mainly because the core concrete limits the circumferential shrinkage of the outer steel tube. The larger the cross-sectional area of CFST specimens is, the higher the bearing capacity is. In this paper, the stress-strain relationship and the overall failure mode of CFST members under tensile force are studied, and the deformation characteristics and stress of steel pipe and core concrete are analyzed, which is expected to provide a reference for the application of CFST specimens in practical engineering.